A)Givenϕ (x) = xe2x
"\\phi '= e^{2x}(1 + 2x)"
If ϕ(x) is a solution to the given equation then it satisfies the equation,
"e^{2x}(1+2x)+axe^{2x}-e^{2x}=0 \\\\\n1+2x+ax-1=0 \\\\\n2x+ax=0 \\\\\na=-2"
B)
Given y(ex+1)=x-1
Differentiating with respect to x
dy ( ex+1) + y(ex) dx = dx
dy(ex+1) = dx ( 1-yex)
"\\frac{dy}{dx} = \\frac{1-ye^{x}}{e^{x} +1}"
Putting this value in the given differential equation
"\\frac{1-ye^{x}}{e^{x} +1}=e^{-x}y+\\frac{ay}{e^{-x}y}+x\\\\"
"\\frac{1-ye^{x}}{e^{x} +1}-e^{-x}y-x" ="\\frac{a}{e^{-x}}"
"\\frac{1-ye^{-x}-y(1+e^x)-x(1+e^x)}{1+e^x}= ae^x \\\\\n\n\\\\\n\n\\frac{1-ye^{-x}-(1+e^x)(x+y)}{e^x(1+e^x)}= a"
Comments
Leave a comment